Analisis Pemanfaatan Sumber Daya Air Panas di Toyabungkah - Aisyah nisrina Imtinan; Nadya Shafira Kurnia Sari; Awma Agril Almira; Maulinda Irianti; M. Javi Nugraha; Nuansa Bayu Segara (Universitas Pendidikan Ganesha, 2026)
This study aims to analyze the characteristics and potential of hot spring resources in Toya Bungkah Village, Bangli Regency, Bali, and formulate strategies for their sustainable utilization as a tourist destination. The research employed a qualitative method with a case study approach. The study site was located in the Batur Natural Hot Spring area, with informants comprising local residents, tourism managers, and both domestic and international tourists. Data were collected through observation, in-depth interviews, and documentation, using interview guides and observation sheets as instruments. Findings revealed that the hot springs have temperatures ranging from 35°C to 43°C and contain minerals such as sulfur, calcium, and magnesium, which are believed to offer health benefits. Utilization includes tourism, hydrotherapy, and support for the local economy, managed by the Batur Traditional Village with a revenue-sharing system that supports cultural and social activities. The challenges identified include insufficient digital promotion, inadequate facilities, and unmanaged environmental risks. Proposed strategies involve strengthening digital marketing, improving infrastructure, training local human resources, and establishing community-based environmental regulations. In conclusion, the utilization of Toya Bungkah hot springs significantly contributes to community welfare but requires well-planned and sustainable management to ensure long-term benefits.